2021
DOI: 10.1021/jacs.1c02545
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Ultrafast Structural Dynamics by Time-Domain Raman Spectroscopy

Abstract: In traditional Raman spectroscopy, narrow-band light is irradiated on a sample, and its inelastic scattering, i.e., Raman scattering, is detected. The energy difference between the Raman scattering and the incident light corresponds to the vibrational energy of the molecule, providing the Raman spectrum that contains rich information about the molecular-level properties of the materials. On the other hand, by using ultrashort optical pulses, it is possible to induce Raman-active coherent nuclear motion of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 140 publications
2
31
0
Order By: Relevance
“…The plasmonic mechanism solely enhances Raman scattering for molecules in close proximity with said plasmons, so a 100 nm-thick film would predominately yield Raman scattering from molecules unassociated with the plasmons of the gold substrate. Indeed, this is reflected in our spectra, which are nearly identical to those of previous Raman studies of bulk TIPS-Pc. , …”
Section: Resultssupporting
confidence: 88%
“…The plasmonic mechanism solely enhances Raman scattering for molecules in close proximity with said plasmons, so a 100 nm-thick film would predominately yield Raman scattering from molecules unassociated with the plasmons of the gold substrate. Indeed, this is reflected in our spectra, which are nearly identical to those of previous Raman studies of bulk TIPS-Pc. , …”
Section: Resultssupporting
confidence: 88%
“…TR-ISRS is a femtosecond time-domain Raman technique, in which a photochemical reaction is initiated by a femtosecond actinic pump pulse, and Raman active vibrations of the transient species are measured in the time domain using ultrashort Raman pump and Raman probe pulses. Fourier transform of the observed time-domain Raman signals provides frequency-domain femtosecond time-resolved Raman spectra that contain rich structural information on the transients. TR-ISRS allows us to monitor structural dynamics on a femtosecond time scale, as has been shown in the studies of a variety of complex molecular systems, including wtGFP . TR-ISRS data of LSSmOrange obtained in this study revealed that two structurally distinct excited states participate in ESPT of LSSmOrange.…”
supporting
confidence: 62%
“…Expanded analyses of EIS responses and other modulated electrooptical techniques applied to organic photoelectrodes will greatly improve our understanding. ,,, Additionally, coupling two or more spectroscopic techniques to explore and monitor the excited state structural and carrier populations, alongside the different photochemical/photophysical processes within these polymer photoelectrodes will provide rich information that will improve our understanding of their inner workings. For instance, performing integrated time-resolved Raman and TAS measurements on polymer photoelectrodes will afford us information on the excited state structural dynamics and charge carrier dynamics, respectively, which are key considerations for the architecture of next-generation efficient photoelectrodes.…”
Section: Charge Carrier Dynamics Of Polymer Photoelectrodesmentioning
confidence: 99%